Respons Pemberian Jamu Fermentasi Terhadap Pertambahan Berat Badan dan Mortalitas Ayam Kampung Periode Pertumbuhan - Sari Gando Hidayati (Fakultas Pertanian Universitas Tamansiswa Padang, 2022)
This research was conducted to study the respons of fermented herbal medicine improve in body weight, and decrease the mortalitas in local chickens, and then determine the best level of for the drinking water mixture of local chickens. This study used 100 local chickens aged 2 weeks and studied for 6 weeks, carried out in the cage of Mr. M. Yusuf Nasution in Jorong III Pertanian, Rao District, Pasaman Regency. The study consisted of 5 treatments, namely P1 (without fermented herbal medicine), P2 (fermented herbal medicine 50 ml / liter drinking water), P3 (fermented herbal medicine 100 ml / liter drinking water), P4 (fermented herbal medicine 150 ml / liter drinking water), and P5 (Fermented Herbal Medicine 200 ml / liter of drinking water). The data obtained were processed using a completely randomized design (CRD) with 5 treatments and 4 replications. The results showed that the local Chickens given fermented herbal medicine had an average feed consumption ranging from 1816.27 to 1881.16 grams. The average weight gain ranged from 468.97 to 6045.89 grams. The average feed conversion ranged from 4.01 to 2.81. and Mortality 0.25%. This study proved to be very significantly different (P <0.01) after the Duncant Multiple Range Test (DMRT) continued test. Based on the results of this study, it can be concluded that the most optimal giving of fermented herbal medicine into the drinking water of native chickens is treatment 4 (fermented herbal medicine 150 ml / liter of drinking water